Gender (in)securities: Surveillance and transgender bodies in post 9/11 era of neoliberalism - Quinan, Christine (Security/mobility: politics of movement, 2017)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; citoyenneté; corps; genre; hétérosexisme; identités; législation; personnes trans*; périodes historiques; queer; racisme; ressource en ligne; solidarité; systèmes d'oppressions; thématiques; violences

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Ni homme ni femme: enquête sur l'intersexuation - Picquart, Julien (L'attrape-corps, 2009)
"Ni homme ni femme est le premier livre, en français et destiné au grand public, à faire le point sur une question quasiment taboue et presque inconnue de la plupart d'entre nous : comment vit-on avec des organes génitaux atypiques ? Pour y répondre, Julien Picquart a rassemblé des témoignages inédits sur le sujet. Quinze personnes racontent leur quotidien, leur parcours, leur vie sentimentale et sexuelle, les traitements hormonaux et chirurgicaux. Les parents témoignent aussi et reviennent sur leurs réactions quand ils ont découvert que leur enfant n'était pas comme les autres. Pour la première fois également, des médecins parlent, de leurs certitudes et de leurs doutes. Toutes ces personnes nous confrontent à leurs interrogations : faut-il ou non opérer ? N'y a-t-il vraiment que deux sexes ? Quelle importance doit-on accorder aux organes génitaux ? Jusqu'où peut aller notre tolérance ? Un ouvrage accessible et profondément humain, qui bouleverse nos certitudes."
Keywords: 1900-1999; 1980-1989; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; premier cycle; périodes historiques; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques; violences

"Because she was my first girlfriend, I didn't know any different": Making the case for mainstreaming same‐sex sex/relationship education - Donovan, Catherine; Hester, Marianne (Sex Education, 2008)
In this paper we present the case for those entering/considering same-sex relationships to be included in sex and relationship education in schools. The Government's Guidance on Sex and Relationship Education provides a rationale for including same-sex relationships when it says that schools should meet the needs of all their pupils "whatever their developing sexuality." Research on sex education and domestic violence prevention for schools has highlighted issues of gender, power, the importance of understanding context in providing skills and knowledge for safer sex and non-abusive relationships. However, both tend to assume the context is heterosexuality. Results from our Economic & Social Research Council-funded study of domestic violence in same-sex and heterosexual relationships indicates that those aged under 25 years of age and those in first same-sex relationships are particularly vulnerable to experiencing domestic violence. Four themes arise from the qualitative data that provide a rationale for the provision of sex and relationship education to these young people: first same-sex relationships as an affirmation of identity; and lack of knowledge about what to expect in same-sex relationships; of embeddedness in lesbian, gay, bisexual, transgender and queer friendship networks; and of resources to seek help.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; approches et analyses; discours dominant; genre; hétérosexisme; identités LGBTQIA2+; inégalités; périodes historiques; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; violences; violences conjugales; éducation sexuelle; étude qualitative

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Pink blood: la violence homophobe au Canada : essai - Janoff, Douglas (Triptyque, 2007)
Essai traduit de l'anglais sous la direction de Diane Archambault Livre unique en son genre, Pink Blood est la première étude de cas de portée nationale à paraître en français sur le thème de la violence homophobe. Fruit de neuf ans de recherche, il couvre plus de 350 agressions et quelque 120 homicides perpétrés au Canada sur la personne de gais et de lesbiennes entre 1990 et 2004. L’ouvrage analyse avec minutie l’impact de la violence homophobe dans une démocratie qui s’enorgueillit d’accorder « l’égalité » à tous ses citoyens… Certains Canadiens seraient-ils plus égaux que d’autres? De Whitehorse à St. John’s en passant par Montréal et Québec, l’auteur pose les questions suivantes: Comment la police fait-elle enquête sur ces crimes et comment les enregistre-t-elle? Quel traitement leur réserve le système judiciaire? Comment les médias présentent-ils ces incidents? Quels programmes et politiques ont soulevé la question de la violence homophobe et transphobe et quels sont ceux qui sont passés à côté de la question? La version anglaise de l’ouvrage, parue en 2005 aux Presses de l’Université de Toronto, a été retenue dans le programme d’enseignement de plusieurs facultés universitaires canadiennes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; histoire et politique; homophobie; hétérosexisme; premier cycle; périodes historiques; régions géographiques; soc2014; systèmes d'oppressions; thématiques; violences

King King théorie - Despentes, Virginie (Grasset, 2006)
J'écris de chez les moches, pour les moches, les frigides, les mal baisées, les imbaisables, toutes les exclues du grand marché à la bonne meuf, aussi bien que pour les hommes qui n'ont pas envie d'être protecteurs, ceux qui voudraient l'être mais ne savent pas s'y prendre, ceux qui ne sont pas ambitieux, ni compétitifs, ni bien membrés. Parce que l'idéal de la femme blanche séduisante qu'on nous brandit tout le temps sous le nez, je crois bien qu'il n'existe pas. V.D.
Keywords: 2000 à aujourd'hui; 2000-2009; anticapitalisme; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; europe; fem1000; fem7000; france; hétérosexisme; identités LGBTQIA2+; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; violences; violences sexistes et sexuelles; études littéraires

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences